Third language acquisition and linguistic transfer - Rothman, Jason; González Alonso, Jorge 1986-; Puig-Mayenco, Eloi 1990- (Cambridge studies in linguistics, 2022)
"Third Language Acquisition and Linguistic Transfer Is acquiring a third language the same as acquiring a second? Are all instances of non-native language acquisition simply one and the same? In this first book- length study of the topic, the authors systematically walk the reader through the evidence to answer these questions. They suggest that acquiring an additional language in bilinguals (of all types) is unique, and reveals things about the links between language and mind, brain, and cognition, which are otherwise impossible to appreciate. The patterns of linguistic transfer and what motivates it when there are choices (as can only be seen starting in third language acquisition) underscores a key concept in linguistic and psychological sciences: Economy. Overviewing the subfields examining multilingual acquisition and processing, this book offers an expanded systematic review of the field of multilingual morphosyntactic transfer, as well as providing recommendations for the future emerging field"-- Provided by publisher.